THEORETICAL FOUNDATIONS OF MARKETING MANAGEMENT IN HIGHER EDUCATION INSTITUTIONS - Khodjayeva Shodiyabonu Abitjanovna (Modern American Journals, 2025)
This article highlights the theoretical foundations of marketing management in higher education institutions. The necessity of forming a marketing strategy for higher education institutions based on the intensifying competition in the education services market, the needs of students, and labor market requirements is analyzed. The article scientifically examines the conceptual approaches, theoretical models of marketing management, and their integration into the educational process.
Keywords: Higher education institutions, marketing management, educational services, brand management, communication policy, value creation model, digital marketing, student needs, international rankings, sustainable development.